2016
DOI: 10.1016/j.lithos.2016.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology and geochemistry of Late Cretaceous–Paleocene granitoids in the Sikhote-Alin Orogenic Belt: Petrogenesis and implications for the oblique subduction of the paleo-Pacific plate

Abstract: ) 'Geochronology and geochemistry of Late CretaceousPaleocene granitoids in the Sikhote-Alin Orogenic Belt : petrogenesis and implications for the oblique subduction of the paleo-Pacic plate. ', Lithos.,[266][267] Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 72 publications
1
31
0
1
Order By: Relevance
“…The above reasoning is reinforced by the finding of the younger granitoids in the Russian Far East, South Korea and Southwest Japan (see [2]). As above, Niu et al [1] concluded that the collision of an alien terrane carried by the paleo-Pacific plate with the eastern continental China at ~ 100 Ma jammed the trench and accreted the basement of the Chinese continental shelf (beneath East and South China Seas), resulting in a new plate boundary to the east between the newly accreted Chinese continental shelf and the paleo-Pacific plate (also see [2]].…”
Section: Observations and Reasoning Towards The Continental Rift Origmentioning
confidence: 90%
See 4 more Smart Citations
“…The above reasoning is reinforced by the finding of the younger granitoids in the Russian Far East, South Korea and Southwest Japan (see [2]). As above, Niu et al [1] concluded that the collision of an alien terrane carried by the paleo-Pacific plate with the eastern continental China at ~ 100 Ma jammed the trench and accreted the basement of the Chinese continental shelf (beneath East and South China Seas), resulting in a new plate boundary to the east between the newly accreted Chinese continental shelf and the paleo-Pacific plate (also see [2]].…”
Section: Observations and Reasoning Towards The Continental Rift Origmentioning
confidence: 90%
“…As above, Niu et al [1] concluded that the collision of an alien terrane carried by the paleo-Pacific plate with the eastern continental China at ~ 100 Ma jammed the trench and accreted the basement of the Chinese continental shelf (beneath East and South China Seas), resulting in a new plate boundary to the east between the newly accreted Chinese continental shelf and the paleo-Pacific plate (also see [2]]. The lack of granitoids of < ~ 90 Ma in the eastern continental China and the greater Chinese continental shelf region is consistent with the new plate boundary being of transform nature with the paleoPacific plate, whose course of spreading changed from the prior NW direction to NNW (i.e., similar to the age-progressive Emperor Seamount Chain of Hawaiian hotspot origin) because of the trench jam and Pacific plate rotation [1].…”
Section: Observations and Reasoning Towards The Continental Rift Origmentioning
confidence: 91%
See 3 more Smart Citations